2020
DOI: 10.21203/rs.3.rs-17302/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of andrographolide in not active Progressive Multiple Sclerosis: A prospective exploratory double-blind, parallel-group, randomized, placebo-controlled trial

Abstract: Background: Multiple sclerosis (MS) is a chronic immune mediated disease and the progressive phase appears to have significant neurodegenerative mechanisms. The classification of the course of progressive MS (PMS) has been re-organized into categories of active vs. not active inflammatory disease and the presence vs. absence of gradual disease progression. Clinical trial experience to date in PMS with anti-inflammatory medications has shown limited effect. Andrographolide is a new class of anti-inflammatory ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Intriguingly, andrographolide has been reported to have a potential neuroprotective effect on CCH‐induced hippocampal neuronal damage and cognitive impairment by inhibiting astrocyte activation and enhancing BDNF TrkB signaling pathway (Wang et al, 2019). A prospective randomized controlled trial of andrographolide in the treatment of inactive progressive multiple sclerosis evidenced that, it has potential research significance in reducing brain atrophy and disability and showed a well‐tolerated by patients, but needs to be further evaluated in larger clinical trials (Ciampi et al, 2020). Besides, andrographolide also delineated excellent effect in protecting hippocampal neurons from injury (Wang et al, 2020) and relieving neuropathic pain (Yi et al, 2018).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, andrographolide has been reported to have a potential neuroprotective effect on CCH‐induced hippocampal neuronal damage and cognitive impairment by inhibiting astrocyte activation and enhancing BDNF TrkB signaling pathway (Wang et al, 2019). A prospective randomized controlled trial of andrographolide in the treatment of inactive progressive multiple sclerosis evidenced that, it has potential research significance in reducing brain atrophy and disability and showed a well‐tolerated by patients, but needs to be further evaluated in larger clinical trials (Ciampi et al, 2020). Besides, andrographolide also delineated excellent effect in protecting hippocampal neurons from injury (Wang et al, 2020) and relieving neuropathic pain (Yi et al, 2018).…”
Section: Pharmacologymentioning
confidence: 99%
“…By analyzing the literatures, it was conjectural that the toxicity of andrographolide was mainly related to the concentration and time of administration. Besides, a clinical trial of andrographolide 140 mg orally twice a day in the treatment of multiple sclerosis demonstrated that it caused mild rash and taste disorder, which executor suggested it need to be further evaluated in a larger clinical trial (Ciampi et al, 2020). More interestingly, in a phase I clinical study of andrographolide in the treatment of HIV, andrographolide was reported to cause mild to moderate headache, fatigue, rash, decreased taste, large diarrhea or pruritus and allergic reactions (Calabrese et al, 2000).…”
Section: Toxicitymentioning
confidence: 99%